1994
DOI: 10.1192/bjp.165.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Inner London Collaborative Audit of Admission in Two Health Districts

Abstract: A 'buffer' of hospital beds in south Southwark may have allowed a more acceptable service, particularly for affective disorders. The possibility that this buffer could be replaced by a wider range of residential accommodation, including hostels away from the District General Hospital, is discussed. Ten recommendations are listed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 47 publications
1
36
1
4
Order By: Relevance
“…The different points of view on appropriate admissions, coupled with variability in risk thresholds between staff, means different wards have differing patient populations (Flannigan et al 1994). Those differences may be accentuated by locality epidemiological and demographic differences.…”
Section: Discussionmentioning
confidence: 99%
“…The different points of view on appropriate admissions, coupled with variability in risk thresholds between staff, means different wards have differing patient populations (Flannigan et al 1994). Those differences may be accentuated by locality epidemiological and demographic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Short lengths of admission have been consid ered to represent low levels of illness and inappropriate admission (Flannigan et al, 1994). If so, junior psychiatrists appear to be good judges of appropriateness of admission, since most admissions considered inappropriate lasted only a few days.…”
Section: Alternative Management Strategy Frequencymentioning
confidence: 99%
“…1986;Kent & Yellowlees, 1994). Attitudes and experience of the admitting doctor also influence the admission process (Meyerson et al, 1979;Flannigan et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot be certain what proportion of the admissions were for people considered to be at risk of suicide, but a study that examined reasons for admission for a number of mental health trusts in London found that for 36%, prevention of suicide was the 'major' (21%) or a 'contributory' (15%) factor. 12 Even if we take only those where it was the major factor (and disregard the fact that some in-patient suicides would not even be identified as belonging to any prevention of suicide group), the rate of in-patient suicide would be around 1 in 285 patients. Presumably for all of these patients, sufficiently apparently suicidal to be admitted to a psychiatric unit, an entirely plausible narrative culminating in a suicide could, with hindsight, have been constructed.…”
Section: Problem 4: the Assessment Of Riskmentioning
confidence: 99%